Some remarks on applications of analogy within intercultural dialogue - Dudek, Agnieszka Helena (Filozofia Publiczna i Edukacja Demokratyczna, 2021)
In this article I present some applications of analogy with reference to intercultural dialogue, firstly as a process in which the familiar structure of a direct experience in one situation improves awareness of an expected experience within another structure. Secondly, I follow the Enrique Dussel’s approach according to which where analogy is the key element of a true dialogue. In the paper conceptions of Ryszard Kapuściński, Martin Buber, Józef Tischner are presented in the context of intercultural dialogue and are applied to Yuko Abe’s analysis of students exchange experiences.